Italian emigration and Italian Language in Costa Rica - Castro-Prieto, Allan (InterSedes, 2021)
In the following article, I present a summary of several aspects of the Italian migration in Costa Rica. First, the typology of Italian migrants, second, a brief description of the language they spoke, third, the diglossic position of languages in their repertoire, fourth, the Italians in Costa Rica, their location of origin in Italy, fifth, their original languages, finally the influence of Spanish and some conclusions found in Franceschi.